2007
DOI: 10.1007/s00122-007-0541-1
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of five resistance genes to sugar-beet powdery mildew using AFLP and anchored SNP markers

Abstract: Sugar-beet powdery mildew, caused by the fungus Erysiphe betae, now occurs in all sugar-beet growing areas and can reduce sugar yield by up to 30%. Powdery mildew resistant plants from three novel sources were crossed with sugar beet to generate segregating populations. Evaluation of resistance was carried out in artificially inoculated field and controlled environment tests. The resistance level in two of the sources was found to be significantly higher than that in currently available sugar-beet cultivars. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…The mapping data also indicated that the Kalundborg population segregates for only one resistance locus. Therefore, we assumed Rz2 and Rz3 to be identical, referring to them as Rz2 (refs 6, 7, 28, 29). …”
Section: Methodsmentioning
confidence: 99%
“…The mapping data also indicated that the Kalundborg population segregates for only one resistance locus. Therefore, we assumed Rz2 and Rz3 to be identical, referring to them as Rz2 (refs 6, 7, 28, 29). …”
Section: Methodsmentioning
confidence: 99%
“…6.8 Synthesis of three-way hybrid variety including tests of combining ability for O-types and pollinators polymorphisms (AFLP); (iv) simple sequence repeats (SSR); (v) single nucleotide polymorphisms (SNP), as well as morphological and isozyme markers (Barzen et al, 1992;Pillen et al, 1992Pillen et al, , 1993Boudry et al, 1994;Barzen et al, 1995;Uphoff and Wricke, 1995;Halldén et al, 1996;Schondelmaier et al, 1996;Nilsson et al, 1997;Schumacher et al, 1997;Hansen et al, 1999;Weber et al, 1999;Rae et al, 2000;Schneider et al, 2001;Möhring et al, 2004;Grimmer et al, 2007a;Schneider et al, 2007). The specific numbering of individual chromosomes, defined in genetic linkage maps, has been standardized.…”
Section: Genetic Mapsmentioning
confidence: 99%
“…Interestingly, a complete class of disease resistance genes, the TIR-type, is completely lacking in B. vulgaris (Tian et al, 2004). QTL approaches have identified chromosome regions associated with resistance to powdery mildew (Grimmer et al, 2007b), rhizoctonia crown and root rot (Lein et al, 2008), rhizomania (Gidner et al, 2005;Lein et al, 2007), Aphanomyces (Taguchi et al, 2009), and cercospora leaf spot Schäfer-Pregl et al, 1999;Setiawan et al, 2000). Generally, the genetic component of these measured traits can be portioned into 2-10 chromosome regions, and many of these could be considered oligogenic in their inheritance patterns.…”
Section: Genetic Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA extraction: Genomic DNA was extracted from snap‐frozen leaf tissue and quantified as described by Grimmer et al. (2007a).…”
mentioning
confidence: 99%